The gender division of work across countries - Gottlieb, Charles,Doss, Cheryl R.,Gollin, Douglas,Poschke, Markus (IZA - Institute of Labor Economics, 2024)
Across countries, women and men allocate time differently between market work, domestic services, and care work. In this paper, we document the gender division of work, drawing on a new harmonized data set that provides us with high-quality time use data for 50 countries spanning the global income distribution. A striking feature of the data is the wide dispersion across countries at similar income levels. We use these data to motivate a macroeconomic model of household time use in which country-level allocations are shaped by wages and a set of
10419/295919
Keywords: Graue Literatur; labor supply; home production; care work; time use; gender inequality; gender norms